Preparation of multifunctional silicon‐phosphorus acrylate particles for the simultaneous improvement of the flame retardancy and mechanical performance of polylactic acid - Gao, Xueyu; Yan, Li; Sang, Xiaoming (Journal of applied polymer science, 2023)
Polylactic acid (PLA) is a biodegradable plastic that currently has limited application owing to its poor fire resistance and brittleness. Herein, a multifunctional silicon‐phosphorus acrylic resin(P/Si‐ACR) is designed to endow both flame retardancy and toughness to PLA. P/Si‐ACR is prepared by seeded emulsion polymerization with polysiloxane as the core layer and diethyl methylphosphonate acrylate and 9, 10‐dihydro‐9‐oxa‐10‐phosphophenanthrene‐10‐oxide acrylate as the shell materials. P/Si‐ACR has a particle size of approximately 200 nm and glass transition temperatures of −38 and 152°C for the core and shell layers, respectively. Addition of 7 wt% P/Si‐ACR to PLA increases the notched impact strength and elongation at break by 124% and 46%, respectively. This improved mechanical performance is due to the elasticity of silicone rubber and the promotion of crystallization by P/Si‐ACR. Combustion testing revealed that the limiting oxygen index increases from 19.1% to 22.5%, while the peak heat release rate decreases by 36%. This enhanced flame retardancy is due to the synergistic effect of phosphorus and silicon, with the former promoting graphitization and inhibiting the free radical degradation of PLA, and the latter stabilizing the char residue. Therefore, P/Si‐ACR is a promising multifunctional modifier that can achieve an optimal balance among flame retardancy, crystallization performance, and toughness in polymers. A multifunctional silicon‐phosphorus acrylic resin (P/Si‐ACR) with a core‐shell structure was synthesized as a modifier for polylactic acid (PLA). Experiments demonstrate that the addition of P/Si‐ACR to PLA increased the notched impact strength and elongation at break. The flame retardancy of PLA also improved significantly with the addition of P/Si‐ACR.